A roll stability performance measure for off-road vehicles. (April 2016) - Yin, Yuming; Rakheja, Subhash; Boileau, Paul-Emile
Highlights: An alternative performance measure for assessing roll stability of off-road vehicles is proposed. The proposed dynamic rollover threshold showed good correlation with the conventional performance measure on smooth road. The vertical and roll excitations generated from off-road terrain adversely affected the vehicle dynamic roll stability. The dynamic rollover threshold was strongly influenced by the lower spatial frequency components of the terrain elevation. Abstract: The roll stability is significant for both road and off-road commercial vehicles, while the majority of reported studies focus on road vehicles neglecting the contributions of uneven off-road terrains. The limited studies on roll stability of off-road vehicles have assessed the stability limits using performance measures derived for road vehicles. This study proposes an alternative performance measure for assessing roll stability limits of off-road vehicles. The roll dynamics of an off-road mining vehicle operating on random rough terrains are investigated, where the two terrain-track profiles are synthesized considering coherency between them. It is shown that a measure based on steady-turning root-mean-square lateral acceleration corresponding to the sustained period of unity lateral-load-transfer-ratio prior to the absolute-rollover, could serve as a reliable measure of roll stability of the vehicle operating on random rough terrains. The robustness of proposed performance measure is demonstrated considering sprung mass center height variations and different terrain excitations. The simulation results revealed adverse effects of terrain elevation magnitude on the roll stability, while a relatively higher coherency resulted in lower terrain roll-excitation and thereby enhanced vehicle roll stability. Terrains with relatively higher waviness increased the magnitude of lower spatial frequency components, which resulted in reduced roll stability limits.